Konstruksi Isu Lingkungan dalam Film Green Warriors: Indonesia The World’s Most Polluted River - Raden Rahadian Firman Akbar (Jurnal Riset Jurnalistik dan Media Digital, 2022)
Abstract. The Citarum River has a few problems from upstream to downstream. The damage and neglect that lasted for years slowly became a threat to the surrounding community. Documentary films as a medium of mass communication in practice record and document people's lives, or raise certain values ​​related to reality. The film Green Warriors: Indonesia The Worlds Most Polluted River tries to record and investigate the problems that occur in the Citarum Watershed (DAS). Based on this, the research questions include: (1) How is the construction of environmental issues in the film Green Warriors: Indonesia seen from the Reality Level; (2) How is the construction of environmental issues in the film Green Warriors: Indonesia seen from the Level of Representation; (3) How is the construction of environmental issues in the film Green Warriors: Indonesia seen from the Ideological Level; (4) What is the narrative structure pattern of the Citarum River problem in the film Green Warriors: Indonesia. The method used in this research is a qualitative method with John Fiske's semiotic analysis approach, through literature study and related documents relevant to the research. Based on the results of the study, it was found: (1) Construction of Environmental Issues in the film at the Reality Level focuses on depicting the community around the Citarum River; (2) Construction of the film's Environmental Issues in the Representation Level focuses on depicting the Citarum River; (3) Construction of Environmental Issues in the film at the Ideological Level focuses on capitalism in the Citarum River area; (4) The Narrative Structure Pattern for the Citarum River problem in the film shows the approach and point of view developed by the filmmaker. Abstrak. Sungai Citarum memiliki sekelumit persoalan dari hulu hingga hilir. Kerusakan dan pembiaran yang berlangsung bertahun-tahun perlahan menjadi ancaman terhadap masyarakat sekitar. Film dokumenter sebagai media komunikasi massa dalam praktiknya merekam serta mendokumentasikan kehidupan masyarakat, ataupun mengangkat nilai-nilai tertentu yang berkaitan dengan kenyataan. Film Green Warriors: Indonesia The Worlds Most Polluted River mencoba merekam serta menyelidiki persoalan yang terjadi di Daerah Aliran Sungai (DAS) Citarum. Berdasarkan hal tersebut, maka pertanyaan penelitian ini antara lain: (1) Bagaimana konstruksi isu lingkungan dalam film Green Warriors: Indonesia dilihat dari Level Realitas; (2) Bagaimana konstruksi isu lingkungan dalam film Green Warriors: Indonesia dilihat dari Level Representasi; (3) Bagaimana konstruksi isu lingkungan dalam film Green Warriors: Indonesia dilihat dari Level Ideologi; (4) Bagaimana pola struktur naratif permasalahan Sungai Citarum dalam film Green Warriors: Indonesia. Metode yang digunakan dalam penelitian ini adalah metode kuallitatif dengan pendekatan analisis semiotika John Fiske, melalui studi pustaka serta dokumen terkait yang relevan dalam penelitian. Berdasarkan hasil penelitian ditemukan: (1) Konstruksi Isu Lingkungan film dalam Level Realitas berfokus pada penggambaran masyarakat sekitar Sungai Citarum; (2) Konstruksi Isu Lingkungan film dalam Level Representasi berfokus pada penggambaran Sungai Citarum; (3) Konstruksi Isu Lingkungan film dalam Level Ideologi berfokus pada kapitalisme pada lingkup Sungai Citarum; (4) Pola Struktur Naratif permasalahan Sungai Citarum dalam film memperlihatkan pendekatan serta sudut pandang yang dikembangkan oleh sineas.